Consumer Perspectives and Certification Barriers: A Case Study at Rumah Makan Uda Denai - Febrian, Adli; Sumarni, Yenti (Halal Science, 2025)
Halal certification plays a crucial role in ensuring food compliance with Islamic law, yet its adoption among small food businesses in Indonesia remains limited. This case report addresses this gap by examining consumer perceptions and identifying the barriers faced by small restaurant owners in pursuing halal certification. The study was conducted at Rumah Makan Uda Denai in Bengkulu City, employing a qualitative descriptive approach. Data were collected through semi-structured interviews, observation, and documentation, involving eight informants. Thematic analysis and data triangulation were employed to ensure the validity of the findings. Findings reveal a spectrum of consumer attitudes, ranging from formal reliance on certification to informal trust in the owner's religious commitment. The primary barrier identified is the owner's limited awareness and understanding of the certification process, which is further compounded by insufficient institutional support. These results underscore the need for targeted outreach and simplified certification mechanisms to support small enterprises. The study contributes to discussions on halal governance in microbusiness settings and highlights practical implications for policymakers and certifying bodies.